2023
DOI: 10.2147/dmso.s400119
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of a Multispecies Probiotic Supplement on Glycaemic Control and Metabolic Profile in Adults with Type 1 Diabetes: A Randomised, Double-Blinded, Placebo-Controlled Pilot-Study

Abstract: Objective In this pilot-study, the effects of a multispecies probiotic supplement on glycaemic control and metabolic parameters in adults with type 1 diabetes (T1DM) were explored. Material and Methods A total of 50 T1DM patients were enrolled and randomly placed into a group receiving capsules containing multi-probiotic strains ( Bifidobacterium longum , Lactobacterium bulagricumi , Streptococcus therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 36 publications
0
16
0
2
Order By: Relevance
“…The effect of MMAs on FCP was reported by five studies with seven subgroups ( n = 336) [ 15 , 29 , 33 , 35 , 37 ], and the reports indicated a significant improvement (SMD = 0.99, 95% CI [0.17, 1.81], p = 0.02) ( Figure 5 ). Sensitivity analysis was performed due to high heterogeneity ( I 2 = 90%, p = 0.01, Tau 2 = 1.00).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of MMAs on FCP was reported by five studies with seven subgroups ( n = 336) [ 15 , 29 , 33 , 35 , 37 ], and the reports indicated a significant improvement (SMD = 0.99, 95% CI [0.17, 1.81], p = 0.02) ( Figure 5 ). Sensitivity analysis was performed due to high heterogeneity ( I 2 = 90%, p = 0.01, Tau 2 = 1.00).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding interventions, one study used a prebiotic (inulin) [ 13 ], two studies used a postbiotic (sodium butyrate) [ 30 , 31 ], one study used a single-strain probiotic ( Lactobacillus rhamnosus GG) [ 32 ], and six used multistrain probiotic or synbiotic supplements [ 29 , 33 , 34 , 35 , 36 , 37 ]. To maximize inclusivity, eligibility criteria did not impose restrictions based on age or the duration of T1D.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations